The Effect of Sambiloto Extract on the Expression of β Estrogen Receptors in Ovaries and Lust Cycle in Mice Model PCOS - Insulin Resistance - Hanis Kusumawati Rahayu (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2021)
Infertility was a serious problem in the reproductive period, one of the caused of infertility were common in women of childbearing age group is Polycystic Ovary Syndrome (PCOS).Sambiloto (Andrographis paniculata Nees), had been already known contain flavonoid and lactones. The purpose of this research had to determine the effect of various doses of sambiloto extract with the expression of β estrogen receptor and estrus cycle in the mice model of PCOS - insulin resistance. This research was an animal model experimental laboratory research with a completely randomized design (CRD).The results showed that sambiloto extract therapy in treatment group had an improvement estrus cycle compared with control group. Positive control group, almost 90% had persistent anestrus condition. In treatment group 1 and 2 in the last vagina smear obtained anestrus condition as much as 60% in diestrus and medestrus phase. Whereas treatment groups 3 all experimental animals in a estrus state by proestrus and estrus phase. β Estrogen receptor expression had tested by Kruskal Wallis test for overall treatment, obtained significantly different results (p ≤ 0.002) followed by Mann - Whitney, showed that immunoreactive cells score from highest to lowest occurred in each group Negative control (KN), P3, P2, P1 and Positive Control (KP). It could be concluded that sambiloto extract at dose 18mg/kgbb, 36mg/kgbb, and 72mg/kgbb had been given an overview of the differences expression of β estrogen receptor, could change the estrus cycle of female mice models of insulin resistance PCOS.